Genetic diversity and allelic frequency of antigenic markers in Plasmodium falciparum isolates from Nnewi district in Nigeria - Ikegbunam, Moses N; Anagu, Linda O; Duru, Carrisa; Nworu, Chukwuemeka S; Esimone, Charles O; Ojurongbe, Olusola (The Journal of Infection in Developing Countries, 2022)
Introduction: The genetic diversity of Plasmodium falciparum poses a threat to the development and implementation of malaria control strategies. Thus, there is a need for continuous surveillance of its genetic diversity, especially amongst the parasite’s reservoir’s asymptomatic population. Methodology: Three cohorts comprising children under ten years old, pregnant women and other adults were recruited into this study. Blood sample was collected from all consenting individuals and screened by the polymerase chain reaction (PCR) method. The genetic diversity of P. falciparum was determined by genotyping the merozoite surface protein-1 (msp-1), merozoite surface protein-2 (msp-2) and glutamate-rich protein (glurp). The size of alleles was visualized on the agarose gel. The multiplicity of infection (MOI) and expected heterozygosity (He) were determined. Results: The majority of the patients showed polyclonal infections, while the multiplicity of infection with msp-2 and glurp of isolates from pregnant women were 2.5 and 1.8, respectively. Children and adults were 2.3 and 1.1; 2.4 and 1.3, respectively. The estimated number of genotypes was 10 msp-1 (4 KI; 4 MAD; 2 RO33), 27 msp-2 (14 FC27; 13 IC/3D7) and 8 glurp. K1 (36/100) was more frequent than the MAD20 (22.33/100) allele, which was, in turn, more frequent than the RO33 (13.59/100). The samples with the 3D7 allele (53.40/100) of msp-2 occurred more frequently than the FC27 type (45.63/100). Polymorphism in the glurp gene occurred most frequently (72.82/100). Conclusion: The study samples exhibited a high degree of genetic polymorphism in msp-2 allele typing with multiple clones, reflecting the complexity of parasite populations.